Performance characteristic of double stator slotted rotor permanent magnet motor - Suhairi, R.; Raja Othman, Raja Nor Firdaus Kashfi; Md Zuki, Nor Aishah; Asyraaf, R.M.; Dezfouli, M.M.S.; Kadir, K.A. (2023)
This paper discusses about the developing a motor-generator machine with the implementation of double stator topology that are used to drive hybrid electric vehicles. In these double stator permanent magnet machines, there are two stator windings which share the same magnetic and mechanical structures to achieve high power density output. A new slotted rotor from ferromagnetic material was used for the double stators in order to maximise the flux produced by the permanent magnet and coil by reducing flux leakage. The implementation of slotted rotor optimised the magnetic flux and evenly distributed the air gap of the inner and outer stator. The Permeance Analysis Method (PAM) for modelling the sizing equation of Double Stator Slotted Rotor Permanent Magnet Motor (DSSR-PMM) reduced computational time. The PAM formulated the sizing equation to calculate the magnetic flux of air gaps in the inner and outer stator. The performance of the DSSR-PMM under motoring mode was analyzed. In the motoring configurations, both inner and outer stator served as the motor. In this research, the numerical design used finite element method (FEM) to validate PAM. The FEM was also used to analyse the characteristics of flux linkage, back EMF, and inductance. For further validation, a prototype of DSSR-PMM was fabricated and tested with various loading conditions to derive the electromagnetic torque, the output power, and the efficiency for the proposed structure. The results from FEM and measurement were verified and they appeared to be in good agreement. The highest efficiency and torque had been achieved of DSSR-PMM were 16.2 Nm and 94 % respectively.